2009
DOI: 10.1111/j.1745-4514.2009.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzymatic Synthesis of Isomalto-Oligosaccharides Production

Abstract: Glucosyltransferases can be applied in the synthesis of prebiotic oligosaccharides. Enzymatic synthesis using acceptors can be used to obtain these carbohydrates. When maltose is the acceptor, oligosaccharides containing one maltose moiety and up to eight glucose units linked by a-1,6glycosidic bonds are obtained as the product of dextransucrase acceptor reaction. In this work, the enzymatic synthesis of isomalto-oligosaccharides using dextransucrase from Leuconostoc mesenteroides NRRL B-512F was optimized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The linear effects of sucrose and reducing sugars were positive and significant for oligosaccharide synthesis. A similar result was obtained by Rabelo et al (2009b) for prebiotic cashew apple juice obtained by fermentation with L. mesenteroides B-512 F. The positive and significant linear effect means that increasing the substrate concentration the oligosaccharide formation is increased. On the other hand, the quadratic effects and the interaction between sucrose and reducing sugar were not significant on the oligosaccharide formation.…”
Section: Enzyme Synthesis Of Oligosaccharidessupporting
confidence: 82%
See 1 more Smart Citation
“…The linear effects of sucrose and reducing sugars were positive and significant for oligosaccharide synthesis. A similar result was obtained by Rabelo et al (2009b) for prebiotic cashew apple juice obtained by fermentation with L. mesenteroides B-512 F. The positive and significant linear effect means that increasing the substrate concentration the oligosaccharide formation is increased. On the other hand, the quadratic effects and the interaction between sucrose and reducing sugar were not significant on the oligosaccharide formation.…”
Section: Enzyme Synthesis Of Oligosaccharidessupporting
confidence: 82%
“…Although the enzyme synthesis was target to oligosaccharides formation, the acceptor reactor is a side reaction of dextran formation and the strategy applied in the present study was enough to shift the enzyme pathway from dextran synthesis to the acceptor reaction because the dextran formed was low compared to the oligosaccharide formation. Rabelo et al(2009b) observed that dextran formation was favored when high concentrations of sucrose and low concentration of reducing sugars was applied. In fact, a low amount of dextran might be beneficial for the final product because dextran is a polysaccharide applied as food thickener that can increase the beverage viscosity (Kassai 2012).…”
Section: Enzyme Synthesis Of Oligosaccharidesmentioning
confidence: 99%
“…The high selectivity and specificity of glucansucrases compared to chemical approaches make them useful synthetic tools for the production of high‐value carbohydrate‐based prebiotics. Optimization studies are underway to economically utilize microbes to maximize enzyme output (Purama & Goyal, ), as well as the enzymes to maximize the generation of OSs (Rabelo, Honorato, Gonçalves, Pinto, & Rodrigues, ). Gluco‐oligosaccharides (GOS) are prepared with the help of glucosyl‐transferases (Dextransucrase (EC 2.4.1.5) and alternansucrase (EC 2.4.1.140) derived from Leuconostoc mesenteroides NRRL B‐512F, which transfer glucose moieties from sucrose to other acceptors (Côté, ; Sanz, Côté, Gibson, & Rastall, ).…”
Section: Prebiotic Oligosaccharides: Influence Of Structure and Effecmentioning
confidence: 99%
“…The high selectivity and specificity of glucansucrases compared to chemical approaches make them useful synthetic tools for the production of high-value carbohydrate-based prebiotics. Optimization studies are underway to economically utilize microbes to maximize enzyme output (Purama & Goyal, 2009), as well as the enzymes to maximize the generation of OSs (Rabelo, Honorato, Gonçalves, Pinto, & Rodrigues, 2009 . However, no significant levels of growth was observed in lactic acid bacteria, Bacteroides, Atopobium cluster, and…”
Section: Glucansucrase Derived Oligosaccharides/glucooligosaccharidmentioning
confidence: 99%
“…immobilized on epoxy produced IMOs (DPs 8-10) from dextran T40 in an enzymatic reactor [68]. A productivity of 42.95 mmol/L.h was obtained using 100 mmol/L of sucrose and 200 mmol/L of maltose, using dextransucrase (1 U/mL) from Leuconostoc mesenteroides NRRL B-512F [69]. A productivity of 7.26 mmol/L.h of IMOs was obtained a using an immobilized mixture of dextransucrase and dextranase [70], while a purified dextransucrase yielded 35 mmol/L.h of panose [71].…”
Section: Alpha-glucan Acting Enzymesmentioning
confidence: 99%